2019
DOI: 10.1155/2019/9292316
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Histopathological Alterations and Trace Metals Estimation of the Small Intestine in Bisphenol A-Intoxicated Rats

Abstract: BPA, a ubiquitously used plasticizer, has become one of the contaminants of emerging concern and causes many serious health implications in humans due to multiple exposure pathways. The current study was aimed at investigating the deformities of structures that arise by exposure of the small intestine to BPA through trace elements estimation of tissues as well as the study of serum profile. Two major groups of Wistar rats were established: one control group and the other experimental group, which was further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In the case of BPA the reduction of the number of gastrointestinal neurons containing acetylcholine, the most important neuronal factor inducing the smooth muscles contraction in the GI tract [ 23 , 44 ], may be based on the relaxant activity of this substance. Namely, it is acknowledged that BPA may impact the intestinal muscles and lead to their relaxation and the inhibition of gastrointestinal motility [ 45 ]. Moreover, fluctuations in the number of nervous structures positive for other substances studied located in the myenteric ganglia and gastric muscular layer can also arise from the relaxant activity of BPA, because all these substances participate in the regulation of digestive tract motility.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of BPA the reduction of the number of gastrointestinal neurons containing acetylcholine, the most important neuronal factor inducing the smooth muscles contraction in the GI tract [ 23 , 44 ], may be based on the relaxant activity of this substance. Namely, it is acknowledged that BPA may impact the intestinal muscles and lead to their relaxation and the inhibition of gastrointestinal motility [ 45 ]. Moreover, fluctuations in the number of nervous structures positive for other substances studied located in the myenteric ganglia and gastric muscular layer can also arise from the relaxant activity of BPA, because all these substances participate in the regulation of digestive tract motility.…”
Section: Discussionmentioning
confidence: 99%
“…Because the main path of toxic infiltration by BPA is via the digestive tract, the stomach and intestine are especially vulnerable to the adverse effects of this substance. The previous studies have indicated that BPA damages the intestinal barrier function and may change nociception in the gastrointestinal tract [5,6]. Moreover, BPA promotes inflammatory processes in the stomach and intestine [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…BPA known as endocrine-disrupting chemical has worldwide application in different plastic products of domestic use. 1 The extensive use of plastic products produce alarming situations and give scientists and environmental protection agencies a new research attention area by understanding the BPA mechanism and its adverse effects particularly on the mammalian body. 26 Accordingly, keeping in view of previous research perspective, current work was designed by taking the objective that how BPA affects splenic architecture and hepatic trace elements and protein profile in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reported endocrine disruptors, bisphenol A (BPA) is one with over six billion pounds production globally each year as a plasticizer. 1 BPA has vast applications in numerous products particularly in the synthesis of polycarbonate, adhesive resins, electrical gadgets, optical glass, paint, thermal papers, food cans, medical equipment, dental sealants, and so on. 2 In the production of vinyl chloride, it is also extensively used as a stabilizer and antioxidant.…”
Section: Introductionmentioning
confidence: 99%